Generation and control of chirped, ultrafast pulse trains - O'Keeffe, K; Robinson, T; Hooker, S (2010)
A method for generating non-uniformly spaced (chirped) trains of high-energy, high-contrast, femtosecond pulses is described and demonstrated. In this method a temporally stretched laser pulse is passed through an acousto-optic programmable dispersive filter (AOPDF), a birefringent plate, and a linear polarizer. It is demonstrated that linear and nonlinear variation of the pulse separation within the train may be controlled by changing respectively the third-and fourth-order dispersion introduced by the AOPDF. Programmable, non-uniform pulse trains of this type may find applications in quasi-phase matching high-harmonic generation. © 2010 IOP Publishing Ltd.